PERCEPTIONS OF CADAVERIC DISSECTION IN ANATOMY TEACHING - Naz, Saima; Nazir, Ghazala; Iram, Samia; Mohammad, Malik; Umair, Umair; Qari, Iftikhar Hussain; Mohammad, Shaheen (Journal of Ayub Medical College Abbottabad, 2011)
Background: Anatomy professors world over are lamenting about medical students' lack of interest in dissections and its diminishing utilisation in medical studies. The objective of our study was to find out the reasons why some of the Pakistani medical students were avoiding dissections. Method: We conducted this study in 5 medical colleges of Pakistan from Dec 2010-Oct 2011. Questionnaires were prepared and administered to more than 500 Pakistani medical students, at least 6 months after their first cadaver dissecting session. Mostly 1st and 2nd year medical students participated in this study. Result: Around 43% students have actually performed dissections in some form, whereas around 57% had never touched the cadaver. Further evaluation of these results revealed that out of 57% of students, 45% avoided dissection due to bad smell of formaldehyde, 37% due to moral/ethical grounds, 22% due to low motivation and respect of human body, 19.4% due to anxiety, 18.6% due to religious reason, 16% due to fear, asthma and emotional reaction, 9.4% due to toxic chemical, 8.6% due to laziness and 7% due to nightmares. Conclusion: In spite of availability of required number of cadavers in all 5 medical colleges and a clear realisation amongst the students that dissecting cadaver is an effective way of learning anatomy; majority of students were not very keen and had therefore not performed dissection even once. Keywords: Anatomy, dissection, cadaver, questionnaire, medical student, formaldehyde